IMPLEMENTING MSME EMPOWERMENT POLICY TO STRENGTHEN BUSINESS COMPETITIVENESS IN OGAN KOMERING ULU REGENCY - Hanny Saykarua; Novita Wulandari; Chitra Imelda (Journal of Governance and Law Reform, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in regional economic development; however, their competitiveness remains constrained by limited managerial capacity, financing access, technology adoption, and market expansion. Although various MSME empowerment policies have been implemented, limited studies have examined how local government implementation processes, organizational capacity, stakeholder coordination, and regional characteristics influence program effectiveness. This study aims to analyze the implementation of the MSME Empowerment Program in improving business competitiveness at the Department of Cooperatives and MSMEs of Ogan Komering Ulu Regency, identify supporting and inhibiting factors, and formulate strategies for strengthening MSME empowerment policies. This study employed a qualitative descriptive approach with a socio-legal and public policy implementation perspective. Data were collected through semi-structured interviews, observation, and documentation involving government officials, MSME actors, cooperatives, and relevant stakeholders. Data analysis was conducted using the Miles, Huberman, and Saldaña interactive model, supported by the Van Meter and Van Horn policy implementation framework. The findings reveal that program implementation is supported by clear policy objectives, institutional commitment, and stakeholder collaboration, but remains constrained by limited resources, uneven mentoring, weak digital adaptation, and outcome-based monitoring limitations. This study contributes to public policy development by proposing a business profile-based empowerment approach that integrates organizational capacity, digital transformation, collaborative governance, and sustainable MSME competitiveness development.